Investigating the psychophysiological effects of NaiKan Therapy: salivary oxytocin and cortisol release - Qian, Ming; Wang, Minghui; Song, Siyi; Xia, Hansong; Huang, Rui; Yuan, Qin; Zhu, Zhi; Wei, Haiyan; Chen, Ming; Ma, Qing; Zhang, Hui (Frontiers in Integrative Neuroscience, 2025)
NaiKan Therapy, a method of self-reflection and introspection, has garnered considerable interest for its psychological benefits. However, its physiological impacts, particularly on hormonal regulation, remain underexplored. In this study, we aimed to investigate the effects of NaiKan Therapy on salivary oxytocin and cortisol release, shedding light on the psychophysiological mechanisms underlying this introspective practice. Sixty participants underwent Naikan Therapy sessions over five consecutive days, during which salivary samples were collected at multiple time points. Salivary oxytocin and cortisol levels were measured using enzyme-linked immunosorbent assay (ELISA) kits. Our results revealed significant increases in salivary oxytocin levels following NaiKan Therapy, suggesting a potential role of this practice in enhancing social bonding and emotional regulation. Conversely, salivary cortisol levels exhibited a decrease post-therapy, indicating a reduction in stress reactivity. These findings provide novel insights into the neuroendocrine mechanisms underlying NaiKan Therapy and highlight its potential as a holistic approach to improving mental wellbeing. Further research exploring the long-term effects of NaiKan Therapy and its implications for clinical practice is warranted.